Handbook of rural studies - Cloke, Paul 1953-; Marsden, Terry 1954-; Mooney, Patrick H. (SAGE, 2006)
Demonstrating how the political economy and the 'cultural turn' have led to significant new thinking in the cultural representations of rurality and related fields, this title explains the key moments in which the theorization of culture nature, politics and space in rural contexts have provided ideas for wider discussion